PMG555 : Research methods / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2018)
This course will explore the process and importance of research in park management and/or natural resource management. This class examines the research process, data collection method, developing data collection instrument, data analysis and writing a research proposal and report.